Proceedings of the 6th Annual ACM Symposium on User Interface Software and Technology 1993
DOI: 10.1145/168642.168658
|View full text |Cite
|
Sign up to set email alerts
|

A toolset for navigation in virtual environments

Abstract: Maintaining knowledge of current position and orientationis frequently a problem for people in virtual environments. In this paper we present a toolset of techniques based on principles of navigation derived from real world analogs, We include a discussion of human and avian navigation behaviors and show how knowledge about them were used to design our tools. We also summarize an informal study we performed to determine how our tools influenced the subjects' navigation behavior. We conclude that principles ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
122
0
10

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(132 citation statements)
references
References 8 publications
(5 reference statements)
0
122
0
10
Order By: Relevance
“…Bowman et al, 2001); breadcrumbs (e.g. Darken and Silbert, 1993); muddy footprints (e.g. Marcus, 1993) among dozens of other have been employed to communicate the designers' intent to the systems' users.…”
Section: Intuitiveness and Familiaritymentioning
confidence: 99%
“…Bowman et al, 2001); breadcrumbs (e.g. Darken and Silbert, 1993); muddy footprints (e.g. Marcus, 1993) among dozens of other have been employed to communicate the designers' intent to the systems' users.…”
Section: Intuitiveness and Familiaritymentioning
confidence: 99%
“…A number of navigational methods have been proposed to help orientation and comprehension in a virtual environment (Darken & Silbert, 1993). In addition, navigational metaphors have been proposed to aide a user's direction-finding in a 3D…”
Section: Navigation Toolsmentioning
confidence: 99%
“…VE trails have presented user's raw movements in the form of virtual footprints, vapor trails, balls of string or breadcrumbs (Darken & Sibert, 1993;Grammenos, Filou, Papadakos, & Stephanidis, 2002;Pettifer, Cook, & Marsh, 2004;Ruddle, 2005). In most cases the trail data has been recorded automatically, rather than expecting a user to specify each waypoint, and this echoes findings from research into information spaces which showed that expecting users to manually identify each item that formed part of a trail was a major limitation of an otherwise successful system (De Roure et al, 2001).…”
Section: Generating Trails Automatically 4 2 Automatically Generated mentioning
confidence: 99%